2012
DOI: 10.1167/iovs.12-9766
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Endothelial Growth Factor Expression by Extra Domain B Segment of Fibronectin in Endothelial Cells

Abstract: These findings showed that high levels of glucose in diabetes increased VEGF expression in ECs through ED-B FN and β1 integrin interaction. These results provide novel mechanistic basis of increased VEGF expression in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…A connection between a2b1 integrin function and VEGF-A induction was first reported by Chen et al, 9 who showed in human umbilical vein endothelial cells that inhibitory antibodies to a2b1 integrin blocked hyperglycemia-induced VEGF-A expression. Our observation of the same phenomena in a distinct cell type (Müller cells as opposed to endothelial cells), in a different species (mouse versus human), with a different stimulus (hypoxia versus hyperglycemia) raises the possibility of a broadly applicable role for the a2b1 integrin in regulating VEGF-A expression.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A connection between a2b1 integrin function and VEGF-A induction was first reported by Chen et al, 9 who showed in human umbilical vein endothelial cells that inhibitory antibodies to a2b1 integrin blocked hyperglycemia-induced VEGF-A expression. Our observation of the same phenomena in a distinct cell type (Müller cells as opposed to endothelial cells), in a different species (mouse versus human), with a different stimulus (hypoxia versus hyperglycemia) raises the possibility of a broadly applicable role for the a2b1 integrin in regulating VEGF-A expression.…”
Section: Discussionmentioning
confidence: 66%
“…[6][7][8] In pathological conditions, overproduction of growth factors, most prominently VEGF, stimulates retinal NV. Chen et al 9 suggest that a2b1 integrin may have an important role in regulating VEGF production in endothelial cells under conditions of hyperglycemia. In the retina, endothelial cells and many other cell types, including astrocytes, retinal pigment epithelial cells, and ganglion cells, contribute to VEGF overproduction; however, animal models have identified Müller cells as the predominant source of VEGF during retinal NV.…”
mentioning
confidence: 99%
“…It might be possible that, in combination with DCN, its conformation and function is also changed [96][97][98]. It has been shown that conformational remodeling of the FN matrix selectively regulates VEGF signaling [121]. VEGF in turn regulates VEGFR2 expression [113].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also identified VEGF-binding sites on fibronectin (Wijelath et al. , 2002, 2006), and fibronectin was shown to regulate VEGF secretion via integrins (Chen et al. , 2012).…”
Section: Discussionmentioning
confidence: 99%